Hemoperitoneum associated with uterine fibroids: A case report. Issue 10 (12th March 2021) - Daimon, Atsushi; Tanaka, Tomohito; Kogata, Yuhei; Tanaka, Yoshimichi; Fujita, Daisuke; Ohmichi, Masahide
Abstract: Introduction: Uterine fibroids, which are common benign tumors, rarely cause acute complications. We herein report a case of hemoperitoneum associated with uterine fibroid that could be diagnosed preoperatively with contrast-enhanced computerized tomography (CT). Patient concerns: A 48-year-old woman with uterine fibroid developed extremely severe lower abdominal pain on the first day of her menstrual period. Diagnosis: Ultrasonography and contrast-enhanced CT revealed a uterine fibroid and extravasation from the dilated vessels of the uterine fibroid. Intervention: Emergent abdominal hysterectomy was performed. Outcomes: The total amount of bleeding was 4, 600 mL. Intraoperative blood salvage (1, 357 mL), 6 units of red blood cells, 4 units of fresh frozen plasma, and 20 units of platelet concentrates were transfused. The postoperative course was uneventful. Pathological examination confirmed a benign uterine fibroid. Conclusion: CT could be useful to determine a diagnosis for bleeding from ruptured subserosal uterine fibroid.